2005
DOI: 10.1074/jbc.m412953200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inhibition of Adipocytogenesis in Human Bone Marrow Stromal Cells Requires Transforming Growth Factor-β/Smad3 Signaling

Abstract: ؉/؉ or Smad3 ؊/؊ mice revealed that the TGF-␤ type I receptor (ALK-5) and its intracellular signaling molecule Smad3 were necessary for the inhibition of adipocyte differentiation by both TGF-␤ and hypoxia-mimetic DFO. Thus, the TGF-␤/Smad signaling pathway is required for hypoxia-mediated inhibition of adipocyte differentiation in MSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 71 publications
6
80
1
1
Order By: Relevance
“…These findings support a recent findings demonstrating that Twist-1 interferes with BMP-2 induced expression of collagen type II and aggrecan [50]. Interestingly, the present study found that adipose accumulation and adipogenic related gene expression were enhanced in human MSC cultures following enforced expression of either Twist-1 or Dermo-1, consistent with studies showing that suppression of osteo/chondrogenesis via BMP/ TGFb signaling is associated with increased adipogenesis [50,[63][64][65][66][67]. Therefore, it is likely that a reciprocal regulation of the Twist transcription factors occurs with different BMP/TGFb and Wnt signaling components that collectively act to regulate the lineage commitment of MSC toward adipogenic or ostechondrogenic development [49,50,62,65,68].…”
Section: Discussionsupporting
confidence: 81%
“…These findings support a recent findings demonstrating that Twist-1 interferes with BMP-2 induced expression of collagen type II and aggrecan [50]. Interestingly, the present study found that adipose accumulation and adipogenic related gene expression were enhanced in human MSC cultures following enforced expression of either Twist-1 or Dermo-1, consistent with studies showing that suppression of osteo/chondrogenesis via BMP/ TGFb signaling is associated with increased adipogenesis [50,[63][64][65][66][67]. Therefore, it is likely that a reciprocal regulation of the Twist transcription factors occurs with different BMP/TGFb and Wnt signaling components that collectively act to regulate the lineage commitment of MSC toward adipogenic or ostechondrogenic development [49,50,62,65,68].…”
Section: Discussionsupporting
confidence: 81%
“…The inhibition by low O 2 tension in the present study was greater in the adipocytes than preadipocytes. Adipocyte differentiation has been shown to be inhibited by incubation under hypoxic conditions and the reduction in PPARg gene expression appears to be a key part of the mechanistic explanation for this (Yun et al 2002, Carriere et al 2004, Kim et al 2005, Zhou et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…They have also been found to secrete increased levels of IL-1b and TNFa in response to leptin (62) . Hypoxia has been shown to inhibit differentiation of mouse preadipocytes, probably as a result of a decrease in PPARg levels (63)(64)(65)(66) . Consistent with this outcome are findings in human preadipocytes in which exposure to hypoxic conditions results in a fall in PPARg gene expression, together with increased HIF-1a protein and GLUT-1 expression (67) .…”
Section: Hypoxia and Insulin Resistancementioning
confidence: 99%